Noncoherent MIMO codes for low-medium SNRs, and layered MIMO space-time coding for coherent and noncoherent receivers - ElMossallamy, Mohamed Ali (AUC Knowledge Fountain, 2016)
Wireless communication systems rely on training the receiver to learn the channel state information (CSI) to communicate information effectively. In these coherent wireless communication systems, pilot signals known to the receiver are sent periodically to help the receiver learn CSI which is needed for effective detection. However, mobile wireless standards are constantly aiming to increase supported velocities and data rates. As the velocity of the receiver increase, the channel changes rapidly, and more frequent training is required, which compromise efficient communication of information. Moreover, multiple-antenna techniques are usually required nowadays to increase supported data rates, which increases the number of channel parameters that have to be estimated and thus requires longer training periods. This lead to significant research activity in wireless communication systems that do not require channel knowledge at the receiver for detection, and thus eliminate the need for training altogether. Those systems are called non-coherent. In the first part of thesis, we propose an new approach to construct space-time codes for the multiple-input multiple-output (MIMO) noncoherent channel. Unlike designs which fixed the number of transmit antennas active at any signaling interval, in our designs we let the number of the active transmit antennas vary over constellation points. We use numerical simulations to evaluate the performance of our proposed designs. At low-to-moderate SNRs, simulations results suggest that our codes could provide significant performance gains over codes designed using direct numerical optimization and exponential mappings where the number of transmit antennas is fixed, especially at higher constellation cardinalities. In the second part, we consider layered space-time signaling over the multiple input multiple output multicast channel. In our proposed scheme, information is encoded in two layers; a low-resolution layer and a high-resolution layer, and there are two classes of receivers; noncoherent receivers that do not have access to accurate CSI and are only able to decode the information in the low-resolution layer, and coherent receivers that have access to accurate CSI, and thus able to decode both the low-resolution and incremental highresolution information. Low-resolution information is encoded using Grassmannian MIMO codes, while high-resolution information is encoded in the indices of the transmitter antennas active during the signaling interval using a scheme called generalized space shift keying (GSSK). The proposed HR layer is completely transparent to the LR layer. Moreover, we propose a computationally efficient two-step decoder. Simulation results suggest that the error performance of the proposed HR layer could be superior to existing schemes that uses conventional space-time codes synthesized from APM symbols and space-time codes designed by direct numerical optimization on the unitary group.